Secure Data Forwarding in Cloud Storage System by using UMIB Proxy - Reddy, P Radha Krishna; Sivaramaiah, S; Sesadri, U (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The cloud storage system is a model consists of networked online collection of storage servers that provides long-term storage services over the Internet hosted by the third parties. Storing data in third party’s cloud system creates serious problems over data confidentiality & authorization. The normal encryption schemes may protect data confidentiality from unauthorized users, but these techniques are limited based on their functionality because only few operations are supported over encrypted data.It’s a challenging task to construct secure storage system with multiple functionalities, if the storage system is distributed. In this paper we developed a secure distributed storage system by using (UMIB-PRE) Unidirectional and Multiuse Identity based proxy re encryption technique with decentralized erasure code. The main theme of this UMIB proxy re encryption is to support encoding, storing and forwarding operations over encrypted data. Our method full supports encryption, decryption, encoding and forwarding techniques. We also suggest possible parameters for these key servers and storage servers as well. These parameters will give robustness to storage servers.